2021
DOI: 10.1159/000513526
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Neonatal QRS Axis during the First Four Weeks of Life

Abstract: Background: The QRS axis represents the sum and orientation of the ventricular depolarization. Accurate interpretation of abnormalities in the QRS axis may facilitate early diagnosis of heart disease in newborns. We aimed at describing the evolution of the QRS axis during the first 4 weeks of life and provide reference values from healthy newborns. Methods: The Copenhagen Baby Heart Study is a prospective general population study that offered cardiac evaluation during the first month of life to all newborns de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(38 reference statements)
4
4
0
Order By: Relevance
“…Rapid changes occur in the cardiac conduction system within the neonatal phase [16,17]. In accordance with previously described association between the QRS axis and postnatal age [16], neonates exposed to multiple maternal/perinatal factors showed a higher postnatal age and a more left-shifted QRS axis.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Rapid changes occur in the cardiac conduction system within the neonatal phase [16,17]. In accordance with previously described association between the QRS axis and postnatal age [16], neonates exposed to multiple maternal/perinatal factors showed a higher postnatal age and a more left-shifted QRS axis.…”
Section: Discussionsupporting
confidence: 88%
“…Rapid changes occur in the cardiac conduction system within the neonatal phase [16,17]. In accordance with previously described association between the QRS axis and postnatal age [16], neonates exposed to multiple maternal/perinatal factors showed a higher postnatal age and a more left-shifted QRS axis. Furthermore, when interpreting QT interval prolongation in neonates examined within first week of life it is important to take into account the high variability of the QT interval within this time period [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Precordial amplitudes and the QRS axis evolve during the first month of life [13, 14], but our findings persisted when subdividing the newborns after age at inclusion. Furthermore, differences between the maternal age groups in newborn, pregnancy, and other maternal characteristics could also confound the results [2, 3, 5, 7, 15‒18], as, e.g., GA has an established association with the QRS axis [14]. Our multivariate regression analysis with adjustment for multiple factors showed that the effect of maternal age on the QRS axis and R-V1 remained significant suggesting a direct effect of maternal age on these two parameters.…”
Section: Discussionmentioning
confidence: 77%